Progress in the solvent depolymerization of lignin. (November 2020) - Patil, Vivek; Adhikari, Sushil; Cross, Phillip; Jahromi, Hossein
Abstract: Solvent liquefaction of lignin is a simultaneous depolymerization and hydrodeoxygenation process used to generate monomer products for fuel and specialty chemical applications. Lignin source, its isolation technique, and the process conditions play essential roles in overall lignin conversion and product distribution. This paper reviews major structural changes that occur during Kraft, organosolv, soda, and other novel lignin extraction processes and how these structural changes affect the solvent liquefaction performances. Reaction conditions, including temperature, residence time, solvent characteristics, and catalyst, are reviewed. Finally, pathways for getting commercially valuable chemicals from lignin is explored. The role of non-water solvents in achieving high-value products from lignin depolymerization is also discussed. The structure of lignin was found to be more critical than reaction conditions in determining the product yields, and future research should have more emphasis on this aspect. Overall, high temperature and longer residence time were found to be useful for depolymerization under certain conditions, such as the presence of homogeneous catalysts, condensed lignin structure, and water as a solvent. Highlights: Reaction conditions affecting the lignin depolymerization mechanism are reviewed. Structure of lignin and its importance in product formation is explored. Challenges in lignin depolymerization and strategies to overcome them are reviewed.